Bi-tubular corrugated composite conical–cylindrical tube for energy absorption in axial and oblique loading: Analysis and optimization. (August 2020) - Sadighi, Amirreza; Mahbod, Mahshid; Asgari, Masoud
In this paper, a new bi-tubular corrugated composite tube, consisting of inner and outer cylindrical and conical tubes is proposed. Different models with various geometrical parameters including the radius of curvatures and their numbers are considered and studied numerically in axial and oblique crushing in order to achieve favorable crashworthiness parameters. Moreover, quasi-static compression tests have been conducted to obtain results in order to validate the finite element model. There has been a sensible agreement between the numerical results and experimental data. Finite element models are also validated using the analytical solutions for both straight and corrugated composite tubes. Regardless of the number and radius of curvatures, as the crashworthiness of bi-tubular corrugated structures both in axial and oblique crushing is investigated and compared with their single-wall and bi-tubular straight peers, a considerable improvement is achieved in all crashworthiness parameters, including desirable increase in specific energy absorption, favorable reduction in peak force, and consequently a beneficial rise in crushing force efficiency. In addition, an optimization study using a suitable multi-objective function is done to choose the best model among the existing models, in addition to finding an optimum model via genetic algorithm. In the next step, a parametric study is conducted on the best model to inspect how well it undergoes oblique crushing at different angles. Finally, this best model and two other candidates have been chosen to investigate the effect of using foams and then the energy absorption capability of the empty and foam-filled tubes has been compared.